Metal on Metal Bearing in Total Hip Arthroplasty and Its Impact on Synovial Cell Count - Henrik C. Bäcker (Journal of Clinical Medicine, 2020)
Introduction: The effect of different bearings on synovial white blood cell (WBC) count and polymorphonuclear percentage (PMN%) in aspirations remains unclear. Therefore, this study investigates the impact of aseptic Metal-on-Metal (MoM) bearing on synovial fluid. Methods: We searched our arthroplasty registry for aseptic painful THAs with MoM bearings between 2011 and 2018. Then, a case-matched control group was selected with septic and aseptic Total Hip Arthroplasty (THA) with ceramic on a polyethylene (PE) bearing. The matching criteria consisted of gender, age +/−10 years, and time of aspiration (+/−2years). Periprosthetic Joint Infection (PJI) was defined according to the Infectious Diseases Society of America (IDSA), and Musculoskeletal Infection Society (MSIS) using bacterial cultures, sonication and histology. Results: In total, 19 patients who underwent hip aspiration with MoM bearing were identified. Five patients had to be excluded due to insufficient synovial fluid obtained (n = 2) or bacterial growth after sonication that was initially negative with the standard microbiological cultures (n = 3). As such, 14 were included. These patients were matched with 14 aseptic and 14 septic THAs with ceramic on a PE bearing, which constituted the control group. The mean serum chrome level was 20.0 ± 15.5 nmol/L and cobalt level 18.4 ± 22.1 nmol/L. The synovial WBC and PMN% varied significantly between MoM bearing group and the aseptic THA ceramic PE group (both p < 0.001), as well as the septic THA group (WBC p = 0.016, PMN% p < 0.001). Furthermore, the septic THA group had significantly higher CRP values than the aseptic MoM group (p = 0.016). Conclusion: MoM bearing shows significantly higher synovial WBC and PMN% when compared to aseptic THA with ceramic on PE bearing above the MSIS cut-off. This is an important consideration when diagnosing periprosthetic joint infection using the MSIS guidelines.